PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENGGELAPAN YANG DILAKUKAN OLEH SALES BARANG ELEKTRONIK OLEH KEPOLISIAN RESOR KOTA PEKANBARU - Hotman Simanungkalit; Erdianto '; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Crime is a social phenomenon that takes place as if endless, there are always new criminal offenses that arise. One crime that began to flourish in the city of Pekanbaru is the crime of embezzlement committed by the sales of electronic goods, where the mode is to darken the electronic items that are under his authority without a prior criminal offense or embezzle money from the sale of the goods. It therefore requires law enforcement against criminal acts committed fraud by sales of electronic goods by Pekanbaru City Police. As for the purpose of this thesis, namely: First, how law enforcement against criminal acts of fraud committed by the sales of electronic goods by the resort city of Pekanbaru police; both barriers experienced Pekanbaru City Police in law enforcement against criminal acts committed fraud by sales of electronic goods; The third attempt was made in overcoming obstacles in law enforcement against criminal acts committed fraud by sales of electronic goods by Pekanbaru City Police.This type of research is classified into types of juridical sociological research. Because in this study the authors directly conduct research in the studied locations in order to get a clear and complete picture of the problem under study, the study was conducted in Pekanbaru City Police. The data used is primary data, the data and the data sekubnder tertiary, data collection techniques using interviews, questionnaires and literature study.From the results of research and discussion authors to conclude that the First, law enforcement against criminal acts committed fraud by sales of electronic goods by Pekanbaru City Police have not run well; Second, barriers experienced in law enforcement against criminal acts of embezzlement by sales of electronic goods by Pekanbaru City Police that a lack of personnel, the distance factor or geographical circumstances, the witness was out of town, limited funding and inadequate facilities; Third, the efforts made to overcome obstacles in law enforcement against criminal acts committed fraud olehsales electronic goods by the City Police Pekanbaru is the addition of personnel, in collaboration with relevant agencies, making the summons and went to the location, to minimize funding and leverage existing infrastructure . Suggestions, Pekanbaru City Police should be more synergy and improve quality, increase legal counseling to entrepreneurs electronics, employers and the public should be more responsive and concerned about education held by the policeKeywords: Law Enforcement-Darkening-Sales-Electronics